Reprogramming of MLL-AF9 leukemia cells into pluripotent stem cells - Liu, Y (Nature Publishing Group, 2014)
The ‘Yamanaka factors' (Oct4, Sox2, Klf4 and c-Myc) are able to generate induced pluripotent stem (iPS) cells from different cell types. However, to what degree primary malignant cells can be reprogrammed into a pluripotent state has not been vigorously assessed. We established an acute myeloid leukemia (AML) model by overexpressing the human mixed-lineage leukemia-AF9 (MLL-AF9) fusion gene in mouse hematopoietic cells that carry Yamanaka factors under the control of doxycycline (Dox). On addition of Dox to the culture, the transplantable leukemia cells were efficiently converted into iPS cells that could form teratomas and produce chimeras. Interestingly, most chimeric mice spontaneously developed the same type of AML. Moreover, both iPS reprogramming and leukemia reinitiation paths could descend from the same leukemia-initiating cell. RNA-seq analysis showed reversible global gene expression patterns between these interchangeable leukemia and iPS cells on activation or reactivation of MLL-AF9, suggesting a sufficient epigenetic force in driving the leukemogenic process. This study represents an important step for further defining the potential interplay between oncogenic molecules and reprogramming factors during MLL leukemogenesis. More importantly, our reprogramming approach may be expanded to characterize a range of hematopoietic malignancies in order to develop new strategies for clinical diagnosis and treatment.